Pesan Dakwah dalam Album Ketika Hati Bicara Karya Ebith Beat *A - Muhammad Tajul Arifin; Atjep Muhlis; - Nase (Department of Islamic Communication and Broadcasting, Faculty of Dakwah and Communication, UIN Sunan Gunung Djati Bandung, 2017)
This study aims to find out the message of da'wah contained in music as well as Ebith songs carried in an album entitled